2021
DOI: 10.1111/head.14094
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative arterial spin labeling magnetic resonance imaging analysis of reversible cerebral vasoconstriction syndrome: A case series

Abstract: Objective: This study aimed to quantify chronological cerebral blood flow (CBF) changes using arterial spin labeling (ASL) magnetic resonance imaging in patients with reversible cerebral vasoconstriction syndrome (RCVS).Background: Quantitative ASL analyses in RCVS have not been well described in the literature.Methods: Quantification of ASL using an automated region-of-interest placement software and a 5-point visual scale of vasoconstriction severity was performed in five RCVS patients. The association betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Arterial spin labeling (ASL) is a perfusion MR technique, which enables cerebral blood flow (CBF) evaluation, without the need for gadolinium injection [80]. According to Kano et al, ASL can infer vasoconstriction in distal vessels "hidden" from MRA by detecting areas of hypoperfusion [94]. In this study, vasoconstriction reached its peak in the second week with subsequent gradual normalization.…”
Section: Imaging In Rcvs and Temporal Relation Of Symptomatology And ...mentioning
confidence: 65%
“…Arterial spin labeling (ASL) is a perfusion MR technique, which enables cerebral blood flow (CBF) evaluation, without the need for gadolinium injection [80]. According to Kano et al, ASL can infer vasoconstriction in distal vessels "hidden" from MRA by detecting areas of hypoperfusion [94]. In this study, vasoconstriction reached its peak in the second week with subsequent gradual normalization.…”
Section: Imaging In Rcvs and Temporal Relation Of Symptomatology And ...mentioning
confidence: 65%
“…Arterial spin labeling (ASL) is a perfusion MR technique, which enables cerebral blood flow (CBF) evaluation, without the need of Gadolinium injection [ 49 ]. Kano et al performed ASL in five patients with RCVS, and it showed higher sensitivity than MR angiography in detecting hypoperfusion [ 50 ]. Vasoconstriction reached its peak in the second week with subsequent gradual normalization [ 50 ].…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…Kano et al performed ASL in five patients with RCVS, and it showed higher sensitivity than MR angiography in detecting hypoperfusion [ 50 ]. Vasoconstriction reached its peak in the second week with subsequent gradual normalization [ 50 ]. Furthermore, it showed a centripetal progression, beginning from distal arteries and affecting the central vessels later.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Sympathetic nervous system hyperactivity causes cerebral vascular dysregulation, which progresses from the peripheral small arteries to the middle and large arteries [ 1 ]. Cerebral perfusion is reduced owing to stenosis of the distal cerebral arteries [ 2 ]. Hypoperfusion causes leptomeningeal artery hyperdilation and causes headache [ 3 5 ].…”
Section: Introductionmentioning
confidence: 99%